Assessing Countries' Financial Inclusion Standing : A New Composite Index. (Washington, D.C. : International Monetary Fund, 2014)
This paper leverages the IMF's Financial Access Survey (FAS) database to construct a new composite index of financial inclusion. The topic of financial inclusion has gathered significant attention in recent years. Various initiatives have been undertaken by central banks both in advanced and developing countries to promote financial inclusion. The issue has also attracted increasing interest from the international community with the G-20, IMF, and World Bank Group assuming an active role in developing and collecting financial inclusion data and promoting best practices to improve financial inclusion. There is general recognition among policy makers that financial inclusion plays a significant role in sustaining employment, economic growth, and financial stability. Nonetheless, the issue of its robust measurement is still outstanding. The new composite index uses factor analysis to derive a weighting methodology whose absence has been the most persistent of the criticisms of previous indices. Countries are then ranked based on the new composite index, providing an additional analytical tool which could be used for surveillance and policy purposes on a regular basis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet